Bootstrap style in T2 multivariable control panels - Hamza Ismail Shaheen; Firas Munther Jassim (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Control charts have been used to monitor processes and detect abnormal behaviors. However, most control charts establish their control limits when the distribution of the observed data is normal . The bootstrap method is a nonparametric technique that does not rely on the assumption of a distribution of the observed data. In this study we have been used a bootstrap in multivariate T2 control chart that can efficiently monitor a process when the distribution of the observed data is non-normal or unknown . A simulation study was conduct to evaluate the performance of the proposed control chart and compare it with a traditional Hotelling’sT2 control chart . The results showed that the control chart using of the bootstrap performed better than the traditional T2 control chart